Surface modification of Cr(III) packaging substrates for enhanced adhesion via citric acid processing - Eifion Jewell (Surfaces and Interfaces, 2020)
Changes in legislation have led to Cr (VI) being removed from manufacturing processes and this has an impact on the production of chromium coated packaging steel products. Novel substrates produced using Cr(III) in the electroplating process are being developed, but have yet to reach the mature functionality of the Cr(VI) substrates. As part of the development of a Cr(III) plated steel substrate the presence of citric acid during the retort process was found to be beneficial to adhesion at the lacquer / substrate interface. At the correct concentration it could negate the presence of the usually corrosion inducing sodium chloride. The use of citric acid as a pre-treatment was subsequently investigated and through optimization it was possible to increase the adhesion performance of the substrate. The operating window of treatment was a function of solution temperature and time with best performance being achieved in 5 mins at 95°C. Over exposure to citric acid had a detrimental effect on substrate / lacquer adhesion. The primary mechanisms of citric acid treatment were identified as iron dissolution and chrome oxidation which enhanced the number of substrate surface bonding sites.